Expression of vascular endothelial growth factor D is associated with hypoxia inducible factor (HIF-1α) and the HIF-1α target gene DEC1, but not lymph node metastasis in primary human breast carcinomas. Issue 8 (27th July 2004) - Currie, M J; Hanrahan, V; Gunningham, S P; Morrin, H R; Frampton, C; Han, C; Robinson, B A; Fox, S B
Abstract : Background: Vascular endothelial growth factor D (VEGF-D) induces angiogenesis and lymphangiogenesis. Nodal metastasis is recognised as a powerful prognostic marker in breast carcinoma, but the molecular mechanisms underlying this process are unknown. Although it has been suggested that VEGF-D may regulate nodal metastasis, this is based largely on animal models, its role in human disease being unclear. Aims: To measure the pattern and degree of VEGF-D protein expression in normal and neoplastic human breast tissues. Methods: The pattern and degree of VEGF-D expression was measured in normal tissue and invasive carcinomas, and expression was correlated with clinicopathological parameters, hypoxia markers, and survival. Because other VEGF family members are affected by oestrogen, whether VEGF-D is regulated by oestrogen in breast cancer cell lines was also assessed. Results: VEGF-D was significantly positively associated with hypoxia inducible factor (HIF-1α) (p = 0.03) and the HIF-1α regulated gene DEC1 (p = 0.001), but not lymph node status, the number of involved lymph nodes, patient age, tumour size, tumour grade, lymphovascular invasion, oestrogen receptor, progesterone receptor, c-erb-B2, or tumour histology (all p>0.05). There was no significant relation between tumour VEGF-D expression and relapse free (p = 0.78) or overall (p = 0.94) survival. VEGF-D expression was enhanced by oestrogen in MCF-7 and T47D breast cancer cells, and was blocked by hydroxytamoxifen. Conclusion: These findings support a role for hypoxia and oestrogen induced VEGF-D in human breast cancer and also suggest that tamoxifen and related oestrogen antagonists may exert some of their antitumour effects through the abrogation of VEGF-D induced function.